2013
DOI: 10.1038/bjc.2013.663
|View full text |Cite
|
Sign up to set email alerts
|

Superselective intra-arterial cisplatin infusion and concomitant radiotherapy for maxillary sinus cancer

Abstract: Background:The purpose of this study was to evaluate the efficacy of superselective cisplatin infusion with concomitant radiotherapy (RADPLAT) for previously untreated patients with the squamous cell carcinoma of maxillary sinus (SCC-MS).Methods:Between 1999 and 2010, 54 patients were given superselective intra-arterial infusions of cisplatin (100–120 mg m−2 per week) with simultaneous intra-venous infusions of thiosulfate to neutralise cisplatin toxicity and conventional radiotherapy (65–70 Gy).Results:One pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
58
3
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(67 citation statements)
references
References 17 publications
4
58
3
2
Order By: Relevance
“…As mentioned elsewhere, their report made no mention of the angiographic technique used or the adequacy of cisplatin infusion into the tumor-feeding artery [7]. Further, HPC patients comprised only a small subgroup of the total study population, and this trial targeted unresectable patients, which meant that it could not assess organ preservation [5].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…As mentioned elsewhere, their report made no mention of the angiographic technique used or the adequacy of cisplatin infusion into the tumor-feeding artery [7]. Further, HPC patients comprised only a small subgroup of the total study population, and this trial targeted unresectable patients, which meant that it could not assess organ preservation [5].…”
Section: Discussionmentioning
confidence: 98%
“…However, a group in the Netherlands reported a multicenter, randomized phase 3 trial, in which HPC was performed for 19% of patients in the intra-arterial group and 18% of those in the intravenous group, and concluded that intra-arterial chemoradiation was not superior to intravenous chemoradiation [6]. However, as several points in association with this trial remain controversial [5,7], we decided to retrospectively examine the indications for RADPLAT, with a particular focus on TN stage, in patients with HPC.…”
Section: Introductionmentioning
confidence: 99%
“…Eight patients (32%) were treated with radiotherapy and concomitant intra-arterial chemotherapy (RADPLAT). The treatment protocol for IV-CRT and RADPLAT has been described elsewhere [3][4][5][6]. …”
Section: Treatment Modalitiesmentioning
confidence: 99%
“…In particular, the use of super-selective arterial infusions of cisplatin with concomitant radiotherapy has become popular for head and neck SCC because of its higher local control rate in advanced cases, especially those in the nasal or sinonasal cavity, oral cavity and pharynx SCCs [2][3][4].…”
Section: Introductionmentioning
confidence: 99%